PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN PUPUK HAYATI PADA BERBAGAI MEDIA TANAM - Willy Andrew Tambunan; Rosita Sipayung; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2014)
Growth and Production of Shallot (Allium ascalonicum L.) to the Application of Biofertilizer in theVariety of Plants Media. The objective of this research was to know growth and production ofshallot (Allium ascalonicum L.) to the application of biofertilizer in the variety of plants media, itwas conducted at Tanjung Selamat, Sunggal, Medan with altitude ± 25 meter above the surface ofsea, began January until April 2012, by using a Randomized Block Design with two factors. Firstfactor was plants media consist of four level : M1 (Ultisol : Sand (2:1)), M2 (Vermicompost : Sand(2:1)), M3 (Ultisol : Vermicompost : Sand (2:1:1)), M4 (Ultisol : Vermicompost : Sand (2:2:1))and the second factor is biofertilizer consist of three level, K1 (100 KG/HA), K2 (200 KG/ha), K3(300 kg/ha). The parameter observed were plant height, tiller number, leaf number, fresh weightbulb per sample, fresh weight bulb per plot, dry weight bulb per sample, dry weight bulb perplot,and clove number per sample. The result showed that plants media treatments influentialsignificantly to parameters : plant height 4-7 week after plant,tiller number 6-7 week after plant,leaf number 3-7 week after plant, fresh weight bulb per sample, fresh weight bulb per plot, and wasnot significantly to parameter plant height 2-3 week after plant, tiller number 2-5 week after plant,leaf number 2 week after plant and clove number per sample. The aplication of biofertilizer andinteraction of plant media and biofertilizer was not significantly to all parameter.Keywords : biofertilizer, plants media, shallot